Pendidikan karakter dalam pembelajaran ilmu pengetahuan sosial di SD Negeri Kota Banda Aceh - Faisal Alam; Rahmat Iqbal; Rifandi Perdana; Maryos Ipaubla; Yusup Maulana (SAP (Susunan Artikel Pendidikan), 2025)
This article discusses the implementation of character education in the Social Sciences subject at SD Negeri 31 Banda Aceh. Character education not only focuses on academic achievement but also on the development of essential moral values, ethics, and social skills. A qualitative study using a case study approach was conducted between January-February 2025, involving six Social Sciences teachers as key informants. The results of the research indicate that the integration of values such as honesty, responsibility, and tolerance through contextual learning and group discussions effectively enhances students’ social awareness. However, limited instructional time and varying levels of student comprehension remain significant challenges. The article also emphasizes the need for active parental involvement in supporting character education, thereby fostering a generation that is not only academically proficient but also possesses moral integrity.